Regional Brain Volumes As Mediators of the Association Between Circulating Omega-3 Fatty Acids and Cognitive Function: The Boston Puerto Rican Health Study. (7th June 2021) - Bigornia, Sherman; Yi, Guan; Kim, Bang-Bon; Zhang, Xiyuan; Scott, Tammy; Bhadelia, Rafeeque; Tucker, Katherine
Abstract: Objectives: To assess the mediating role of regional brain volume in the relationship between circulating very-long-chain omega-3 fatty acids and global cognitive function. Methods: Data are from individuals of the Boston Puerto Rican Health Study with a T1-weighted MRI brain scan available approximately 8 y from the baseline visit ( n  = 200, mean age at baseline = 54.7 y, 77.5% female). Red blood cell fatty acid composition was measured at baseline and very-long-chain omega-3 fatty acid was defined as the sum of EPA and DHA. A battery of 7 cognitive tests was administered at baseline and 8-y follow-up in the language of preference. Global cognitive function was the average z-score of the cognitive tests. Whole MRI brain volumetric measures (of cortical and subcortical grey matter) were quantified using the FreeSurfer processing pipeline. Structural equation modeling was conducted to examine the mediating effect of regional brain volumetric measures on the association between omega-3 fatty acid concentration and global cognitive function. Bivariate associations were assessed by age- and sex-adjusted partial Spearman's rho correlation coefficient with FDR correction. Results: The association between baseline omega-3 fatty acid concentration and 8-y global cognitive function was mediated by several cortical regions including the left caudal middle frontal gyrus, right inferior parietal lobes, and right isthmus of cingulate gyrus. Significant mediators in the subcortex included the putamen, amygdala, left ventral dorsal tract, and right thalamus. Omega-3 fatty acid concentration was positively correlated with global cognitive function ( r s  = 0.17, P  < 0.05) and with brain regions identified as significant mediators ( r s  = 0.17 to 0.21, P  < 0.05 for all). Greater volume of the brain region mediators was associated with higher global cognitive function score ( r s  = 0.17 to 0.24, P  < 0.05 for all). Conclusions: These results suggest that, among older Puerto Rican adults, greater circulating omega-3 fatty acids may be related to better cognitive function and that this relationship may be explained by maintenance of specific cortical and subcortical brain regions. Funding Sources: NIA R01AG055948.